Artificial Aurora Produced by HAARP. Issue 5 (15th May 2019) - Tulegenov, B.; Streltsov, A. V.; Kendall, E.; McCarrick, M.; Galkin, I.
Abstract: We present results from the ionospheric heating experiment conducted at the High Frequency Active Auroral Research Program (HAARP) facility, Alaska, on 12 March 2013. During the experiment, HAARP transmitted in the direction of the magnetic zenith X‐mode 4.57‐MHz wave. The transmitted power was modulated with the frequency of 0.9 mHz, and it was pointed on a 20‐km spot at the altitude of 120 km. The heating (1) generates disturbances in the magnetic field detected with the fluxgate magnetometer on the ground and (2) produces bright luminous spots in the ionosphere, observed with the HAARP telescope. Numerical simulations of the 3‐D reduced magnetohydrodynamic (MHD) model reveal that these effects can be related to the magnetic field‐aligned currents, excited in the ionosphere by changing the conductivity in the E region when the large‐scale electric field exists in the heating region. Key Points: We present results from the experiment involving heating the ionosphere with X‐mode HF wave These results show that heating produces magnetic field disturbances and luminous structures Three‐dimensional simulations reveal a connection between observations and magnetic field‐aligned currents